Evaluation of an intracapsular technique for the treatment of cranial cruciate ligament rupture - Geels, J. J.; Roush, J. K.; Hoskinson, J. J.; McLaughlin, R. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
Treatment of cranial cruciate ligament (CCL) rupture using fascial replacement techniques have yielded good clinical results, with 85% to 93% of dogs returning to clinical soundness or intermittent lameness as evaluated by surgeons or owners, but have not been evaluated by force plate analysis long-term. The purpose of this study is to document the long-term clinical and radiographic outcome of dogs having CCL rupture stabilized with an underand- over fascial graft technique by owner assessment, clinical examination, force plate analysis, plain film radiography, and scintigraphy. Twenty dogs with previously repaired unilateral CCL rupture were used for the study. Although client satisfaction was high, force plate analysis revealed significantly lower vertical forces and impulses in the operated versus unoperated limbs. Radiographs and bone scans revealed significant bony changes and synovitis in the operated stifle relative to the unoperated stifle at a median of 17.5 months following repair. Lameness persists in dogs having undergone CCL repair using the under-and-over fascial graft technique; whether this lameness is secondary to progression of osteoarthritis or is a result of surgical repair is unknown.The under-and-over fascial strip technique for stabilization of cranial cruciate ligament-deficient stifles has been evaluated using force plate analysis and nuclear scintigraphy. A median of 17.5 months following surgery, dogs are bearing less weight on the operated limbs as compared to the unoperated limbs. Significant synovitis and bony changes are present when compared to the unoperated limb as evaluated by scintigraphy. Despite these changes, clients are satisfied with the results of surgical repair.
Keywords: Cranial cruciate ligament; ground reaction force; scintigraphy; stifle; surgical management; under-and-over fascial graft